El acceso a la cátedra. Inventario de oposiciones a cátedras jurídicas. 1859-1983 - Díaz Rico, Javier Carlos (Historia del Derecho, 2021)
This book contains a documental inventory of administrative records of the public examinations to Spanish law professorships within the period 1859-1983 arranged chronologically based on the date of announcement. The catalogue, which includes 494 records stored in the in Archivo General de la Administración and in the Archivo Central de Educación (Alcalá de Henares, Madrid), describes the essential elements of the public examination records: archive's signature, professorship denomination, university, date of announcement, applicable regulation, examiners, candidates, votes, nomination and materials.